A call to action: MTHFR polymorphisms should not be a part of inherited thrombophilia testing. Issue 4 (8th June 2022) - Deloughery, Thomas G.; Hunt, Beverley J.; Barnes, Geoffrey D.; Connors, Jean M.; ,
Abstract: Testing for polymorphisms in the methylenetetrahydrofolate reductase (MTHFR) gene is still a standard part of thrombophilia testing in many laboratories. However, it is clear that these polymorphisms are not risk factors for arterial or venous thrombosis and therefore should not be part of thrombophilia testing. Eliminating MTHFR from thrombophilia testing will reduce patient concerns and health care costs.